IMPROVEMENT OF BASIC LIFE SUPPORT (BLS) FROM HAZARDOUS MATERIALS IN FARMERS: PENINGKATAN BASIC LIFE SUPPORT (BLS) DARI BAHAN BERBAHAYA PADA PETANI - Rizeki Dwi Fibriansari; Arista Maisyaroh; Eko Prasetya Widianto (Akademi Keperawatan Yarsi Samarinda, 2020)
Identification of threats, vulnerabilities and ability of farmers in integrated nursing care-based emergency nursing in Lumajang District results in emergency risk results are still high and the ability of integrated farmers emergency response is still low. Management for integrated emergency risk reduction for farmers is needed by enhancing the capacity of farmers and reducing threats and vulnerabilities in agricultural areas. The purpose of this study is to improve the ability of farmers to provide basic life support (BLS) due to hazardous materials to farmers in Lumajang Regency. This study used a pre-post-test design method. Participants in this study were 30 participants who were selected by random sampling. Data analysis was performed using SPSS and hypothesis testing using the Wilcoxon Signed Rank Test with statistical test results p-value = 0,000 (α less than 0.05). This can show that there is a significant capacity improvement after conducting basic life support training due to hazardous materials to farmers.